2017
DOI: 10.1007/s10753-017-0684-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Exerts Anti-oxidative and Anti-inflammatory Effects in Acute Lung Injury

Abstract: Acute lung injury (ALI) caused by septic stimuli is still a major problem in critical care patients. We have shown previously that hydrogen sulfide (HS) mediates anti-inflammatory and lung protective effects. In the present study, we aimed to investigate the underlying mechanisms. C57BL/6N mice were instilled with lipopolysaccharide (LPS) intranasally in the absence or presence of inhaled HS for 6 h. LPS instillation led to alveolar wall thickening, an elevated ALI score, increased neutrophil transmigration, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 39 publications
2
40
0
Order By: Relevance
“…Additionally, cysteine (cys) which is an intermediate in this pathway, serves as the precursor for the formation of glutathione which is the most potent biological antioxidant. Both cystine (the disulfide of cys) and cystathionine are also the sources for the formation of hydrogen sulfide, a gaseous molecule which has been shown to have anti-oxidative, vasodilatory and antiinflammatory properties in addition to several other benefits [67,68]. Most importantly, Met by itself has been shown to have anti-oxidative properties [32,45,47].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, cysteine (cys) which is an intermediate in this pathway, serves as the precursor for the formation of glutathione which is the most potent biological antioxidant. Both cystine (the disulfide of cys) and cystathionine are also the sources for the formation of hydrogen sulfide, a gaseous molecule which has been shown to have anti-oxidative, vasodilatory and antiinflammatory properties in addition to several other benefits [67,68]. Most importantly, Met by itself has been shown to have anti-oxidative properties [32,45,47].…”
Section: Discussionmentioning
confidence: 99%
“…In order to evaluate possible (pre)treatment options, we and others have previously shown that inhalation of hydrogen sulfide (H 2 S) prevents neutrophil accumulation in models of ventilator- 7 9 and lipopolysaccharide (LPS)-induced lung injury 10 14 . Although recent data suggest that H 2 S may limit neutrophil activation and transmigration by downregulating pulmonary expression of chemoattractant molecules 15 or by reducing leukocyte rolling and adhesion 15 18 , it remains completely unknown how H 2 S interacts with the neutrophilic inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, absence of CSE expression promotes AHR. 29 Exogenous administration of H 2 S has been demonstrated as protective in ventilator-induced lung injury, 68,69 acute lung injury, [70][71][72][73][74] hypoxia/hyperoxia environments, [74][75][76] and during acute viral illnesses. [77][78][79] Compared to these data, there is currently no information on H 2 S in the developing bronchial airways per se.…”
Section: Discussionmentioning
confidence: 99%